Histopathologic Findings in Peripheral Vestibular System From Patients With Systemic Lupus Erythematosus: A Human Temporal Bone Study. Issue 10 (December 2015) - Kariya, Shin; Hizli, Ömer; Kaya, Serdar; Hizli, Pelin; Nishizaki, Kazunori; Paparella, Michael M.; Cureoglu, Sebahattin
Abstract : Hypothesis: We hypothesized that a pathologic condition exists in vestibular hair cells in human temporal bones from patients with systemic lupus erythematosus (SLE). Background: A significant association between sensorineural hearing loss and autoimmune disease has been reported. Patients with SLE also frequently have vestibular symptoms whose pathophysiologic mechanism is unclear. Methods: We examined 15 temporal bone samples from 8 patients with SLE, along with 21 samples from 17 age-matched healthy control patients. The samples were serially sectioned in the horizontal plane and stained with hematoxylin and eosin. Using differential interference contrast microscopy, we counted the number of type I and type II hair cells in the saccular macula, the utricular macula, and the cristae of the three semicircular canals; then, we calculated the hair cell density (cells per 0.01 mm 2 ). Results: The mean density of type I hair cells in our SLE group was significantly lower than in our control group in the saccular macula, in the utricular macula, and in the superior, lateral, and posterior semicircular canals. But in all five vestibular sensory epithelia, the mean density of type II hair cells did not significantly differ between our two groups. In our SLE group, the mean density of vestibular hair cells did not significantly correlate with the patient's age at death or with the duration of SLE. Conclusion: Type I hair cells in peripheral vestibular organs are affected in patients with SLE. Our findings could provide a pathologic basis for the difficulty with balance experienced by patients with SLE.